Analysis of Reporting Trends of Serious Adverse Events Associated With Anti‐Obesity Drugs - Branislava B. Raičević; Andrej Belančić; Nikola Mirković; Slobodan M. Janković (Pharmacology Research & Perspectives)
ABSTRACT Concern over the side effects of anti‐obesity medications, particularly if severe, has grown as their use has increased. Thus, the objective was to use trends in the reporting of suspected adverse events associated with anti‐obesity medications that have been approved for sale in the European Union to attempt to uncover discrepancies in the safety of these medications. The study was designed as secondary research, based on data about the number of adverse drug reactions (both serious and non‐serious) reported to the EudraVigilance database. Trends of the annual reporting rates for the six anti‐obesity drugs were analyzed by the Joinpoint Trend Analysis Software that divides the trendline into an optimum number of segments connected by “joinpoints” and tests the significance of the trend within each segment. The trends of serious adverse drug events showed clear differences among the anti‐obesity drugs: while all drugs had significant increasing trends during a few initial years after their appearance on the market, only the annual number of reports for semaglutide continued to grow ever since (annual change + 67.1%, p = 0.000). On the contrary, a continuous increase in the reporting rate of non‐serious adverse drug events was observed only for liraglutide (annual change + 33.8%, p = 0.000) while for the other anti‐obesity drugs, including semaglutide, the trends after the initial period were either negative or did not increase significantly. In conclusion, among the anti‐obesity drugs currently approved, only semaglutide shows a continuously increasing trend in the annual reporting of serious adverse events, suggesting a need for further investigation of safety signals.